PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU VIRTUAL LABORATORY DITINJAU DARI HASIL BELAJAR DAN KEMAMPUAN BERPIKIR LOGIS SISWA SMP - Astutik, Heny Sri; Aniningsih, Putri (Journal of Honai Math, 2019)
This research aims to test the effectiveness of the Problem Based Learning (PBL) learning model. The subjects of this study were 38 of eighth-grade students of Muhammadiyah Middle School Aimas, Sorong Regency, West Papua. The research used a quasi-experimental method, using Nonequivalent Control Group Design. The experimental class uses the PBL learning model by applying VR Math, while the learning control class is carried out with conventional models, namely lectures and frequently asked questions. The instruments used for data collection were observation, tests, and questionnaires. The test instrument consisted of learning outcomes tests and students' logical thinking abilities. The other instrument is questionnaire for students' responses to PBL learning using the VR Math application. The results of the study concluded that the PBL learning model using the VR Math application is not effective if measured from student learning outcomes, conversely, the PBL learning model uses the VR Math application effectively when considered from students' logical thinking abilities.